2020
DOI: 10.3389/fmicb.2020.00283
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro Photoinactivation of Helicobacter pylori by a Novel LED-Based Device

Abstract: The rise of antibiotic resistance is the main cause for the failure of conventional antibiotic therapy of Helicobacter pylori infection, which is often associated with severe gastric diseases, including gastric cancer. In the last years, alternative non-pharmacological approaches have been considered in the treatment of H. pylori infection. Among these, antimicrobial PhotoDynamic Therapy (aPDT), a light-based treatment able to photoinactivate a wide range of bacteria, viruses, fungal and protozoan parasites, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…However from the appearance of totally destroyed cells of S. aureus [ 16 ], significant leakage of intracellular substance in A. baumannii [ 27 ] as well as disrupted cell walls, and complete loss of cytoplasmic components at higher doses in C. albicans [ 28 ] , and release of intracellular components of Listeria monocytogenes and P. fluorescens after 4 days of exposure to visible light [ 29 ], it was concluded that membrane permeability must play an important role in photoinactivation processes. Scanning electron microscopy images depicted structures that looked like holes on Helicobacter pylori after 9.3 J/cm 2 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However from the appearance of totally destroyed cells of S. aureus [ 16 ], significant leakage of intracellular substance in A. baumannii [ 27 ] as well as disrupted cell walls, and complete loss of cytoplasmic components at higher doses in C. albicans [ 28 ] , and release of intracellular components of Listeria monocytogenes and P. fluorescens after 4 days of exposure to visible light [ 29 ], it was concluded that membrane permeability must play an important role in photoinactivation processes. Scanning electron microscopy images depicted structures that looked like holes on Helicobacter pylori after 9.3 J/cm 2 [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The crucial part of every PhotoMIC assay is the irradiation. Nowadays, dental curing lights ( Nielsen et al, 2015 ) or handmade LED setups ( Morici et al, 2020 ) replaced previously used light bulbs and lasers ( Calin and Parasca, 2009 ). Dental lights – originally designed to polymerize composite fillings – allow only single irradiation and, therefore, limit the throughput.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cyclodextrin with bound porphyrins has been applied for the treatment of Staphylococcus aureus (Hanakova et al, 2014). Endogenous porphyrins were utilized for the killing of pathogenic periodontal bacteria (Cieplik et al, 2014;Hope et al, 2016), skin pathogens St. aureus (Ashkenazi et al, 2003;Lipovsky et al, 2009), Staphylococcus carnosus (Hoenes et al, 2020), Hemophilis parainfluenzae (van der Meulen et al, 1997) and Helicobacter pylori (Hamblin et al, 2005;Morici et al, 2020).…”
Section: Discussionmentioning
confidence: 99%